Use of essential drugs: model list of essential drugs (seventh list): fifth report (WHO GenevaCH, 1992)
Presents guidelines for establishing a national programme for essential drugs. Based on these guidelines, a model list is put forward as a means of assisting countries in identifying their own priorities and to make their own selection.
DC